2010
DOI: 10.1016/j.ridd.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou smear screening of women with intellectual disabilities: A cross-sectional survey in Taiwan

Abstract: Although little is known about the incidence of cervical cancer in women with intellectual disabilities (ID), Pap smear screening is an effective public health program to prevent cervical cancer to this group of people. The purposes of this study were to identify and evaluate the factors regarding the utilization of the Pap smears in women with ID seen in the preventive health screening program. We employed a cross-sectional survey "2009 National Survey on Preventive Health Use and Determinants among People wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…In addition, DM patients must undergo regular health checks; therefore, they have more contact with paramedics and are more likely to receive Pap smear tests following the advice or information provided by paramedics. Regarding the severity of disability, the usage rate of mildly disabled people was substantial, which conforms to the findings of a study conducted in 2010 on women with intellectual disabilities [30]. For primary care givers or paramedics, communication difficulties may occur when administering Pap smear tests to women with severe intellectual disabilities.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, DM patients must undergo regular health checks; therefore, they have more contact with paramedics and are more likely to receive Pap smear tests following the advice or information provided by paramedics. Regarding the severity of disability, the usage rate of mildly disabled people was substantial, which conforms to the findings of a study conducted in 2010 on women with intellectual disabilities [30]. For primary care givers or paramedics, communication difficulties may occur when administering Pap smear tests to women with severe intellectual disabilities.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with the general population in Taiwan, women with intellectual disability in the less than 35 years age group were less likely to undergo screening, whereas women in the at least 35 years age group were more likely to undergo a Pap smear test than women in the general population [28 ]. Chou et al [29] conducted an in-depth interview of 55 women with intellectual disability aged 21-65 years; they concluded that women's experiences of perimenstrual symptoms were similar to those of women without intellectual disability, and that their menstrual management, interpretations and attitudes to menses were influenced by their institutional life and by society at large.…”
Section: Preventive Care Usementioning
confidence: 88%
“…) and cervical cancer (Lin et al . ) is reduced among adults with ID, for reasons such as misperceptions, lack of awareness and apprehension (Ward et al . ; Truesdale‐Kennedy et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, the consensus in the literature is that those with ID do have reduced access to health screening. In the case of cancer screening, various studies demonstrate that uptake of screening for breast cancer (Sullivan et al 2003) and cervical cancer (Lin et al 2010a) is reduced among adults with ID, for reasons such as misperceptions, lack of awareness and apprehension (Ward et al 2010;Truesdale-Kennedy et al 2011;Wilkinson et al 2011). Fewer studies have been carried out on the uptake of screening for cardiovascular risk factors, although a study by Janicki et al (2002) suggested that underreporting of the prevalence of cardiovascular risk factors among adults with ID might be due to reduced access to screening.…”
Section: Introductionmentioning
confidence: 99%